A phosphorylation‐deficient ribosomal protein eS6 is largely functional in Arabidopsis thaliana, rescuing mutant defects from global translation and gene expression to photosynthesis and growth - Anwesha Dasgupta; Ricardo A. Urquidi Camacho; Ramya Enganti; Sung Ki Cho; Lindsey L. Tucker; John S. Torreverde; Paul E. Abraham; Albrecht G. vonArnim (Plant Direct, 2024)
Abstract The eukaryote‐specific ribosomal protein of the small subunit eS6 is phosphorylated through the target of rapamycin (TOR) kinase pathway. Although this phosphorylation event responds dynamically to environmental conditions and has been studied for over 50 years, its biochemical and physiological significance remains controversial and poorly understood. Here, we report data from Arabidopsis thaliana, which indicate that plants expressing only a phospho‐deficient isoform of eS6 grow essentially normally under laboratory conditions. The eS6z (RPS6A) paralog of eS6 functionally rescued a double mutant in both rps6a and rps6b genes when expressed at approximately twice the wild‐type dosage. A mutant isoform of eS6z lacking the major six phosphorylatable serine and threonine residues in its carboxyl‐terminal tail also rescued the lethality, rosette growth, and polyribosome loading of the double mutant. This isoform also complemented many mutant phenotypes of rps6 that were newly characterized here, including photosynthetic efficiency, and most of the gene expression defects that were measured by transcriptomics and proteomics. However, compared with plants rescued with a phospho‐enabled version of eS6z, the phospho‐deficient seedlings retained a mild pointed‐leaf phenotype, root growth was reduced, and certain cell cycle‐related mRNAs and ribosome biogenesis proteins were misexpressed. The residual defects of the phospho‐deficient seedlings could be understood as an incomplete rescue of the rps6 mutant defects. There was little or no evidence for gain‐of‐function defects. As previously published, the phospho‐deficient eS6z also rescued the rps6a and rps6b single mutants; however, phosphorylation of the eS6y (RPS6B) paralog remained lower than predicted, further underscoring that plants can tolerate phospho‐deficiency of eS6 well. Our data also yield new insights into how plants cope with mutations in essential, duplicated ribosomal protein isoforms.